2023
DOI: 10.1186/s43066-023-00294-4
|View full text |Cite
|
Sign up to set email alerts
|

Can probiotics play a role in Helicobacter pylori (H. Pylori) eradication?

Sameh Mohamed Fakhry,
Mohamed Abdel-Hameed Kandyl,
Adel Ferig Hashish
et al.

Abstract: Background H. Pylori is one of the commonest infectious diseases worldwide. In recent years, PPI-based triple therapy has been described to be losing its efficacy against H. pylori due to high rates of antibiotic resistance, antibiotics-associated side effects, and low compliance. Probiotics are suggested to improve the H. pylori eradication rate when added to H pylori therapy. Probiotics have anti-inflammatory and anti-oxidative mechanisms that may improve bowel microecology and interact with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Additionally, it causes vitamin (vitamin A, B, C, K, α-tocopherol, vitamin B12, and folic acid) insufficiency in the human body [116][117][118]. Various studies revealed that H. pylori extinction treatment regimens have raised the possibility of several pathogenic microbes such as Streptococcus, Klebsiella, and Shigella [119,120]. These pathogens instigate chronic inflammation and promote the synthesis of genotoxins or carcinogenic metabolites [121][122][123].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it causes vitamin (vitamin A, B, C, K, α-tocopherol, vitamin B12, and folic acid) insufficiency in the human body [116][117][118]. Various studies revealed that H. pylori extinction treatment regimens have raised the possibility of several pathogenic microbes such as Streptococcus, Klebsiella, and Shigella [119,120]. These pathogens instigate chronic inflammation and promote the synthesis of genotoxins or carcinogenic metabolites [121][122][123].…”
Section: Discussionmentioning
confidence: 99%
“…The growing prevalence of antibiotic resistance and the decrease in patient compliance with traditional treatment further illustrate the need for alternative therapies. Fakhry et al (2023) found that patients who received probiotics ( Lactobacillus and Bifidobacterium ) in addition to regular medicine (triple treatment) had a higher percentage of H. pylori eradication than those who received only conventional therapy. Adding probiotics reduced diarrhea as a side effect of antibiotic treatment.…”
Section: Alternative Therapiesmentioning
confidence: 99%